Peranan Mitral Leaflet Separation Index (Mlsi ) dalam Menentukan Severitas Stenosis Mitral - I Made Junior Rina Artha; Amiliana M Soesanto; Indriwanto Sakidjan; Ganesja M Harimurti (The Indonesian Heart Association, 2015)
Objective. To Correlate MLSI with 3-D mitral valve area (MVA) planimetry in determining mitral stenosis (MS) severity.Background. Mitral Stenosis (MS) is still a major problem in cardiology, and causes of morbidity dan mortality worldwide. Echocardiogrphy plays an important role in assessing mitral stenosis severity. Mitral leaflet separation index (MLSI) is one of simple method that can be used in peripheral by using common ultrasound to assess the severity mitral stenosis.Methods. We employed a cross sectional study. Mitral stenosis patients who referred for evaluation echocardiography in National Cardiac Center Harapan Kita from April to September 2011. MLSI was obtained by averaging the maximal leaflet separation distance at the tips in diastole in parasternal long-axis and apical four- chamber views. 3-Dimensional (3-D) mitral valve area (MVA) planimetry as a reference. The only exclusion criteria was severe calcification and poor echo window. Echocardiography examination using Philips E33i.Results. Seventy six consecutive patients were enrolled, 5 subjects were excluded from study because of severe calcification and poor echo window. Proportion of woman is 73.2 % and mostly in age group < 40 years old (43.7 %). Severe mitral stenosis was dominate the subject, 47 subject (66.2 %), moderate was 19 subject (26.8 %), and mild only 5 subjects (7.0 %). Analysis with Spearman correlations obtained a good correlation with r = 0.70, p < 0.001, good correlation was found in sinus rhythm with r = 0.78, p < 0.001 and atrial fibrillation with r = 0.79, p < 0.001. MLSI less than 0.69 cm predicted severe MS with 85 % sensitivity and 82.4 % specificity.Conclusions. Mitral leaflet separation index (MLSI) has a good correlation with 3-D MVA planimetry. MLSI less than 0.69 cm can estimate severe SM.